Physical Education an play - Sandoval Magalhaes, Richard William (2014)
This paper tries to investigate, discover, explore, verify, and verify the importance of educational games in school physical education for moral and spiritual. Nace also the current concern to provide students a way to learn children are our future. If we teach them tolerance, cooperation and solidarity, they will be fair, sensitive and supportive. Therefore, critical-constructive capacity will be higher. This raises an education whose achievement is a new man in a society that is essential, the mode setting personal and social behavior authentically human and full development of the personality. Implementing the contributions of educational technology, allowing them to share a truly liberating education that not only is based on dialogue, critical thinking, participation, autonomy, but also in the play and creativity that promotes the emergence and comprehensive training of students. All studies in the world of children agree on the influence of recreational activity is for the balanced development of children, their psycho-motor, cognitive, affective and social.